The Effectiveness of Illinois Agility Test in Improving Agility of Soccer Athletes Football Deltras FC - Syahbana, Duan Dito; Pamungkas, Hari; Kurniawan, Rubbi; Pradipta, Anangga; Aofal, Reza (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to test the effectiveness of Illinois Agility Test training in improving agility and motor reaction of Deltras FC soccer athletes. Agility and motor reaction are important physical components in soccer that affect the player's ability to make quick changes of direction and respond optimally to the movement of the opponent and the ball. This study used an experimental method with a pretest and posttest design involving two groups the experimental group that received Illinois Agility Test training and the control group that underwent conventional agility training. The data obtained were analyzed using a paired t-test to determine significant differences between the pre-test and post-test in each group. The results of the analysis showed that there was a significant increase in agility and motor reaction in the experimental group compared to the control group (p < 0.05). The average Illinois Agility Test time of the experimental group experienced a greater increase compared to the control group. Likewise in the motor reaction test where the experimental group showed a faster response increase compared to before the intervention